Heterogeneity and Geographical Patterns of PD-L1 Positive Tumor Infiltrating Immune Cells in Colonic Adenocarcinoma. (28th October 2020) - Messersmith, L; Williams, G; Broadwater`, D R; Brady, R
Abstract: Introduction/Objective: Programmed death-ligand 1 (PD-L1) status is an important prognostic and predictive biomarker. PD-L1 status is difficult to accurately assess in tumor cells (TCs) due to tumor heterogeneity and lack of standardized histologic evaluation. PD-L1 expression by tumor infiltrating immune cells (TIICs) is an independent prognostic marker and may provide fewer diagnostic challenges, as TIICs appear less heterogeneous. We examined the geographical patterns of PD-L1 expression in TCs and TIICs in order to evaluate heterogeneity and ease of histological evaluation. Methods: 197 blocks of colonic adenocarcinoma from 33 patients were retrospectively reviewed and stained for PD- L1. PD-L1 was interpreted as positive or negative in the TCs and TIICs. Geographical patterns of expression were recorded for the TCs and the TIICs at the surface, center of tumor, and invasive margin. Geographical patterns were compared using a chi-square test. Results: 56% of blocks had PD-L1 positive TCs. 42.7% showed positive TCs at the invasive margin. 38.2% had positive TCs at the invasive margin and surface. No blocks had positive TCs at the center of the tumor. 79% of blocks had PD-L1 positive TIICs. 20% showed positive TIICs at the invasive margin. 37.4% had positive TIICs at the surface and invasive margin. 15.5% of TIICs expressed PD-L1 throughout the tumor. There was a statistically significant difference in PD-L1 expression on TCs versus TIICs in 4 of the 7 geographic patterns. Conclusion: PD-L1 expression on TCs of colonic adenocarcinoma is more heterogeneous than PD-L1 expression by TIICs. TIICs express PD-L1 more consistently throughout the tumor and are easier to identify and report. PD-L1 expression by TIICs is an independent prognostic indicator and may be more useful than TCs when evaluating the tumor microenvironment and determining PD-L1 status.